Radiological Assessment of Artisanal Mining Sites in Michika Local Government Area, Adamawa State - Y, Yusuf E.; N, Maitera O.; U, Moddibo U.; M, Buba One (African Journal of Medicine, Surgery and Public Health Research, 2025)
The proliferation of artisanal mining activities in Michika Local Government Area (LGA) of Adamawa State, Nigeria, has raised serious environmental and radiological safety concerns due to the presence of naturally occurring radioactive materials (NORMs), particularly uranium-238 (U-238) and thorium-232 (Th-232). This study assesses the radiological hazards associated with these activities by analyzing soil samples collected from ten artisanal mining sites using gamma-ray spectrometry. The results revealed that the mean activity concentrations of U-238 and Th-232 were 1187.85 Bq/kg and 1052.20 Bq/kg, respectively substantially exceeding the global average values of 33 Bq/kg and 45 Bq/kg recommended by UNSCEAR (2000). Potassium-40 (K-40) was below detectable levels, likely due to the geochemical composition dominated by minerals such as monazite, zircon, and phosphate-rich rocks. The mean absorbed dose rate was 1184.32 nGy/h, significantly higher than the global average of 57 nGy/h, while the estimated mean annual effective dose equivalent (AEDE) was 1.45 mSv/year, surpassing the 1 mSv/year public exposure limit. The mean radium equivalent activity (Ra_eq) reached 2692.50 Bq/kg, far above the recommended safety limit of 370 Bq/kg. Additionally, the calculated excess lifetime cancer risk (ELCR) averaged 0.005084, markedly higher than the acceptable threshold of 0.00029. Other radiological indices, including the Representative Level Index (RLI), Internal Hazard Index (H_in), and External Hazard Index (H_ex) also recorded values exceeding international safety standards, particularly at sites like Sina Mala and Garta. These findings underscore the urgent need for regulatory enforcement, radiological monitoring, and the adoption of sustainable and safe mining practices to mitigate health risks for both miners and local communities.